SAT0410 Musculoskeletal Flares and Development of Hand Deformities in Systemic Lupus Erythematosus: A 5-Year Clinical and Ultrasonographic Prospective Follow-up Study. (9th June 2015) - Piga, M.; Gabba, A.; Figus, F.; Congia, M.; Cauli, A.; Mathieu, A.
Abstract : Background: The majority (70-80%) of SLE patients develop non-deforming arthritis, but in 5-15% of cases joint involvement progresses to deforming arthropathy classified as non-erosive, the so-called Jaccoud's arthropathy (JA), or erosive on X-ray, the so-called rhupus syndrome (RH). Objectives: To assess the incidence of and risk factors for musculoskeletal flares and development of deforming or erosive arthropathy in SLE patients through a 5-year prospective follow-up study. Methods: At baseline, 108 consecutive patients with past or present musculoskeletal involvement, fulfilling at least 4 of the 1997 ACR criteria for SLE, were recruited and underwent clinical, X-ray and ultrasound (US) examination. Visits were scheduled every 6 months or according to clinical needs. Each patient was classified as affected with RH by satisfying 1987 criteria for Rheumatoid Arthritis, with JA according to the modified Jaccoud's articular index (JAI) or with non-deforming non-erosive (NDNE) arthropathy. The occurrence of musculoskeletal flares was assessed at each visit using the musculoskeletal item of BILAG2004 index. Clinical, serological findings registered at visit preceding musculoskeletal flare and US results registered at baseline were used as covariates. Clinical and serological findings registered at baseline were used as covariates to identify risk factors related to development of hand deformities (according to JAI) and US erosions (according to the OMERACT definition), which were assessed comparing baseline versus study end findings. Stepwise logistic regression models were fitted with covariates with p<0.1 to predict outcomes; p<0.05 was considered significant. Odds ratio (OR) with 95% confidence interval (95% CI) was calculated. Results: Ninety-one patients (mean age 43.1±13.4 years; disease duration 10.7±7.3 years) completed the 5-year follow-up. In 975 clinical assessments, 25 musculoskeletal flares (8 "A" severe and 17 "B" moderate) in 17 (18.6%) patients (10 NDNE, 4 RH, 3 JA) were recorded. High level of CRP (p=0.014 OR 5.4; 95%CI 1.4-20.9) and US evidence of synovial proliferation with power-Doppler signal in joints or tendons (p=0.009 OR 9.9; 95%CI 1.6-34.8) were independently associated with risk of musculoskeletal flare; patients classified as NDNE have lower risk (p=0.008; OR 0.1 95%CI 0.01-0.56). New US erosions were detected in 18 (19.7%) patients (14 NDNE, 3 RH, 1 JA); X-ray confirmed the erosive pattern only in the 3 patients with RH. The only independent risk factor for development of new US erosion was high level of CRP (p=0.006; OR 4.4 95%CI 1.5-13.1). Development or worsening of hand deformities was detected in 7 (8.6%) patients (5 NDNE, 1 RH, 1 JA). Longer disease duration (p=0.0087; OR 1.2 95%CI 1.1-1.3), high level of CRP (p=0.031; OR 15.8 95%CI 1.2-195.2) and musculoskeletal flares during follow-up (p=0.034; OR 3.3 95%CI 1.0-10.0) were independent risk factors for development of hand deformities. Conclusions: High levels of CRP and positive US power-Doppler signal identify SLE patients with higher risk for musculoskeletal flares. CRP is also a marker of erosive and deforming musculoskeletal damage accrual. Development of hand deformities was more likely in patients with higher number of musculoskeletal flares and longer disease duration. Disclosure of Interest: None declared